The management of challenges related to the innovation process: a multi-case study in industries of the cosmetic sector - Gonzalez, Inayara Valéria Defreitas Pedroso (Revista de Administração da UFSM, 2020)
Purpose – The objective was to reveal reflections on how the managers of industrial cosmetic companies deal with the challenges related to the innovation process. Design/methodology/approach – Exploratory qualitative research. The present research uses a combination of methods: theoretical-conceptual, bibliographical survey and the multi-case study, by means of the following procedures: semi-structured interview, observation route and document analysis. Findings – I concluded that the main challenges faced by the management of the innovation process in the small business are related to the non-development of a culture focused on innovation and not planning the capacity to decentralize. In the case of the medium sized company, the main challenge related to the innovation process is to manage, simultaneously, the growth of the company on the one hand, and the managerial practices aimed at the use of the knowledge of its team, on the other, in the process of innovation. In the case of the large company, I concluded that the challenges of maintaining the integration of the innovation process and, at the same time, the flexibility to transform the way things are done, are well orchestrated by management because there is constant discussion and shared vision, in a spirit of trust and teamwork. Research limitations/implications – The data cannot be generalized because it is a multi-case study. Practical implications – As soon as the challenges were identified, the assumption was confirmed that the achievement of innovation implies knowing how to integrate resources and capacities, manage periods of instability or irregularity and regularity, based on a culture focused on strategic learning, learning to learn and, systemic learning. Originality/value - This exploratory qualitative research contributes with evidences and analyzes on the management of the innovation process in three companies of different sizes, in which are revealed the managerial actions in relation to the innovation requirements that have been explored from the theoretical bases that support the integration of the learning organizational and management of innovation, and the reflections on how manifest the management of the challenges faced in each company.